2023
DOI: 10.3390/nano13061056
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Output Performance of a Triboelectric Nanogenerator Based on Modified Polyimide and Sandwich-Structured Nanocomposite Film

Abstract: Recently, scientists have been facing major obstacles in terms of improving the performances of dielectric materials for triboelectric nanogenerators. The triboelectric nanogenerator (TENG) is one of the first green energy technologies that can convert random mechanical kinetic energy into electricity. The surface charge density of TENGs is a critical factor speeding up their commercialization, so it is important to explore unique methods to increase the surface charge density. The key to obtaining a high-perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…7a and Table S1. †, 43,[52][53][54][55][56] As an energy conversion device, stability during operation is crucial for practical application. Herein, a durability test was also conducted under 5 Hz contact frequency for the 200 FPP@Nano NY TENG, and the results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7a and Table S1. †, 43,[52][53][54][55][56] As an energy conversion device, stability during operation is crucial for practical application. Herein, a durability test was also conducted under 5 Hz contact frequency for the 200 FPP@Nano NY TENG, and the results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it has been experimentally and theoretically proven that self-assembled PFTS can effectively improve the output of polypropylene-based triboelectric nanogenerators. in recent years that use structural design and surface chemical modification to improve the output of contact-separation mode triboelectric nanogenerators, it was found that by combining the design of double nanostructures and chemical modification methods, the charge density obtained in this work can achieve a relatively higher value as shown in Figure 7a and Table S1 43,[52][53][54][55][56] . As an energy conversation device, the stability during operation is crucial for practical application.…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 99%
“…As noted in the literature, the typical procedure applied in the electrical output improvement of TENGs is based on the direct relationship between electrical performance and surface roughness [24][25][26][27][28] that contributes to the improvement in the available area [26] for the accumulation of high charge density at interfaces. However, it is worth mentioning that highly rough surfaces in TENGs can return a decrease in the contact area between the two triboelectric surfaces [29]. Consequently, under the controlled creation of nanoand micro-roughness patterns, it is possible to optimize the output performance, being considered a limiting condition for reducing the contact area of tribolayers [29].…”
Section: Thermal and Structural Characterization Of Cb And Modified C...mentioning
confidence: 99%
“…However, it is worth mentioning that highly rough surfaces in TENGs can return a decrease in the contact area between the two triboelectric surfaces [29]. Consequently, under the controlled creation of nanoand micro-roughness patterns, it is possible to optimize the output performance, being considered a limiting condition for reducing the contact area of tribolayers [29]. In addition to the roughness degree, an important aspect to be considered is the dielectric layer doping technology methods [30] based on the incorporation of high dielectric permittivity (ZnO and TiO 2 ), creating the effect of dispersion of nanocapacitors that reinforce the interface polarization.…”
Section: Thermal and Structural Characterization Of Cb And Modified C...mentioning
confidence: 99%
“…Despite these limitations, TENGs have garnered significant attention from research groups seeking to overcome these challenges and improve their output performance for various energy harvesting applications [204]. The benefits of TENGs are extensive and include their sustainable energy harvesting capabilities from converting abundant wasted mechanical energy resources into electrical energy [205] and their low capital cost [238], durability [239], suitability for self-powered devices [240], robust structure [241], compact size for human healthcare applications [242], sustainability for biomedical microsystems [74], flexibility [243], sensitivity in biochemical sensor diagnostics [244], portability [245], lightweight design [246], eco-friendliness [247], green energy conversion abilities [248], multifunctionality for self-powered sensors [249], smart features [250], high material availability for fabrication, simple structure, and compatibility with a variety of trigger sources in nature [202,203]. Numerous research efforts have focused on utilizing TENGs for self-powered sensing applications.…”
Section: Benefits Challenges and Solutionsmentioning
confidence: 99%